2020
DOI: 10.3390/agriculture11010017
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Business Model Innovation vs. “Made in” for International Performance of Italian Food Companies

Abstract: The quality of Italian food products, linked to Made in, has always been a competitive driver within foreign markets. However, today, getting quality choices also means engaging in responsible behavior. The paper investigates the relation between the choice of environmental and social standards and the international performance of a set of agri-food firms in Italy, examined through the multiple case study method and the tools of qualitative methodology. What role do standards play in attributing an added value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Some authors have recently studied sustainable competitiveness in some specific sectors, such as tourism (Nadalipour et al, 2019), energy (Mills et al, 2021), agriculture (Qtaishat et al, 2022;Kucher, 2020), agri-food (Constantin et al, 2023). Meanwhile, studies on "sustainable international competitiveness" are very scarce and recent (Ghag et al, 2023;Tang et al, 2022;De Chiara, 2020). In the agro-export sector, De Chiara (2020) showed that the adoption of environmental and social criteria by Italian agri-food companies was the result of innovation processes, which in turn had a positive influence on their international competitiveness performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors have recently studied sustainable competitiveness in some specific sectors, such as tourism (Nadalipour et al, 2019), energy (Mills et al, 2021), agriculture (Qtaishat et al, 2022;Kucher, 2020), agri-food (Constantin et al, 2023). Meanwhile, studies on "sustainable international competitiveness" are very scarce and recent (Ghag et al, 2023;Tang et al, 2022;De Chiara, 2020). In the agro-export sector, De Chiara (2020) showed that the adoption of environmental and social criteria by Italian agri-food companies was the result of innovation processes, which in turn had a positive influence on their international competitiveness performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, despite the issue of the links between CSR&P is a well-known general issue (Kang and Liu, 2014;Klassen and Vereecke, 2012;Waddock and Graves, 1997;Wang and Choi, 2013), literature devoted to CSR&P in the agri-food sector mainly investigates impacts of CSR on performance (CSR→P) in terms of both direct (De Chiara, 2021;Martos-Pedrero et al, 2019;Nirino et al, 2020) and indirect (Weber and Saunders-Hogberg, 2020) impacts.…”
Section: Introductionmentioning
confidence: 99%